Ranking of process safety cultures for risk-based inspections using indicative safety culture assessments. (March 2020) - Zwetsloot, Gerard; van Kampen, Jakko; Steijn, Wouter; Post, Sjoerd
Abstract: Although major hazard industries have no legal obligations to demonstrate a good safety culture, it is an increasingly important factor for risk-based inspections. This paper describes the development and evaluation of a relatively simple method for external indicative assessment of the process safety culture in major hazard industries. As a first step, a tool was developed. Second, the tool was successfully tested in a workshop with major hazard inspectors. After this 'proof of concept' and a few adaptations to improve the tool, quantitative evaluation and validation were carried out with a representative sample of major hazard inspectors in the Netherlands. In this stage, the tool comprised 30 questions, of which 19 sufficiently frequent valid responses were given for the validity test. The evaluations demonstrate that without specific preparations, inspection teams can use the tool to discriminate between plants with poor or good safety cultures. That is sufficient for ranking as additional input for risk-based inspection strategies. The resulting indicative 'scores' for safety culture correlate meaningfully with the quality of process safety management systems and the number of (legal) non-compliances, which were identified by the inspection team at the same occasion. The use of the tool can be further improved by training inspectors, making minor adaptations of the inspection process, and broadening the scope of a few questions. It is expected that external assessments of safety culture will become increasingly important not only for inspectorates, but also for a range of other external stakeholders. Highlights: An indicative process safety culture assessment tool was developed and tested. The indicative safety culture assessment tool focuses on practices around 14 aspects of culture. Inspectorates can use the tool for ranking safety cultures and improving risk-based inspection strategy. Indicative process safety culture scores per company were meaningfully correlated to compliance. External assessments of safety culture are becoming increasingly important for the license to operate.